2018
DOI: 10.3390/proteomes6040037
|View full text |Cite
|
Sign up to set email alerts
|

Fyn Regulates Binding Partners of Cyclic-AMP Dependent Protein Kinase A

Abstract: The cAMP-dependent protein kinase A (PKA) is a serine/threonine kinase involved in many fundamental cellular processes, including migration and proliferation. Recently, we found that the Src family kinase Fyn phosphorylates the catalytic subunit of PKA (PKA-C) at Y69, thereby increasing PKA kinase activity. We also showed that Fyn induced the phosphorylation of cellular proteins within the PKA preferred target motif. This led to the hypothesis that Fyn could affect proteins in complex with PKA. To test this, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Similar effects are realized through Csk downstream in T cell activation ( Vang et al, 2001 ) and vascular sprouting ( Jin et al, 2010 ). Importantly, as has been shown for the EGF receptor ( Caldwell et al, 2012 ), Src family kinases can phosphorylate PKA and this modification increases its catalytic activity ( Schmoker et al, 2018 ).…”
Section: Targets Of Pka Activitymentioning
confidence: 95%
See 1 more Smart Citation
“…Similar effects are realized through Csk downstream in T cell activation ( Vang et al, 2001 ) and vascular sprouting ( Jin et al, 2010 ). Importantly, as has been shown for the EGF receptor ( Caldwell et al, 2012 ), Src family kinases can phosphorylate PKA and this modification increases its catalytic activity ( Schmoker et al, 2018 ).…”
Section: Targets Of Pka Activitymentioning
confidence: 95%
“…In the reverse direction, tyrosine phosphorylation of PKA by Fyn increases PKA activity and changes PKA complexing with binding partners such as AKAPs and phosphodiesterases, which further complex with Fyn in a glioblastoma cell line ( Schmoker et al, 2018 ).…”
Section: Targets Of Pka Activitymentioning
confidence: 99%
“…While other tyrosine kinases such as EGFR and Fyn have been shown to directly phosphorylate the PKA catalytic domain [35, 36], these modifications lead to only a modest increase in the catalytic efficiency of PKA in vitro , and the direct PKA phosphorylation by FAK has not been investigated. Thus, while phosphorylation of PKA subunits by FAK has not been shown, it is possible that FAK, like EGFR and Fyn, may directly modify and thus regulate PKA catalytic subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Though it is uncommon, it is not unheard of for a tyrosine kinase to regulate PKA activity. Both receptor tyrosine kinases and Src family kinases have been shown to regulate PKA activity by phosphorylating the PKA catalytic subunit directly [35, 36]. However, this work has been largely conducted in vitro and has not yet extended to FAK.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the discovery that SKIP is indeed enriched at the inner mitochondrial membrane where it associates with Chchd3, a prominent PKA substrate (Means et al, 2011). In HEK293 cells, immunoprecipitation of YFP-labelled PKA catalytic subunit (PKACα) was used to characterise the cross-talk between cAMP and Src family kinase signalling (Schmoker et al, 2018). Results from these experiments demonstrated that the activity of the Src family kinase Fyn influences the docking of PKA to specific cellular scaffolds and suggest that Fyn may affect the downstream substrates targeted by PKA.…”
Section: Using Chemical Proteomics and Interactomes To Define Camp Simentioning
confidence: 99%